PENGARUH SKALA INDUSTRI TAHU TERHADAP EFISIENSI DI DESA PRODUKSI DI KELURAHAN BANJAREJO, KECAMATAN TAMAN, KOTA MADIUN - Rekyani Puspitawati, Indah (JURNAL AGRI-TEK, 2017)
Agroindustry always means adding value. Similarly, the food management industry. With good system and management method, agroindustry will increase the added value of processed agricultural products so that the result can penetrate the market. One food polishing industry that plays a role in the absorption of labor in rural areas is the soybean processing industry in the form of tofu industry. Industry has a large enough population and generally in the form of household industry. To know more about the role of tofu industry at different business scale level, it is necessary to do research on “Influence of Industrial Scale To Know Efficiency in Production in Banjarejo Village , Taman Sub-district, Madiun City”. Research Objectives, among others: To know the income level of home industry know at various business scale. To know the absorption of labor of home industry know at various business scale. To know the productivity of the workforce of home industry know at various business scale. To know the feasibility level of home industry know at various business scale. The study used the method of analysis and its implementation by survey technique. Method of determining the research area using purposive sampling method that is in District Banjarejo. Determination of the number of samples using snow ball sampling method. The data used are primary data and secondary data. Technique of collecting data is done by recording, observation and interview. The results showed that profitability of household industry know the scale of small business average in one month Rp. 2,281,514.63 with B/C Ratio of 1.17. This shows that the industry knows in Kelurahan Banjarejo in Madiun City Beneficial and feasible because B/C ratio is greater than 1. A business is feasible to use if the value of B? C Ratio> 1 and a business is not feasible to use when the value of B/C Ratio <1. Keywords : Efficiency, business scale, production, income